PEMBELAJARAN MORAL MELALUI PEMBELAJARAN KOOPERATIF - Muslih, Moh. (IAIN Pekalongan, 2010)
The development of moral learning through cooperative learning aims to produce students who are good, having moral, who understand, and able to exercise the rights and obligations both as a human being living in society as well as citizens of Indonesia. Assessment of moral learning through cooperative learning is relevant and necessary in the era of globalization which demands competition and impacts on the emerging attitude of exclusivism, permisivisme, and secularism. Cooperative learning has some advantages not only in boosting student academic achievement, but can also encourage the social aspects of treatment such as respecting others, empathy with others, cooperate with others and reduce the various negative aspects of competition, as well as able to give impressions on some other positive behaviors. However, to implement cooperative learning takes good preparation and planning therefore teaching and learning process can be carried out effectively and efficiently.